Autofluorescence imaging videobronchoscopy improves assessment of tumor margins and affects therapeutic strategy in central lung cancer - Zaric, Bojan; Becker, Heinrich D.; Perin, Branislav; Stojanovic, Goran; Jovelic, Aleksandra; Eri, Zivka; Panjkovic, Milana; Ilic, Miroslav D.; Matijasevic, Jovan; Antonic, Milan (Japanese journal of clinical oncology, 2010)
Autofluorescence imaging (AFI) videobronchoscopy is a new endoscopic tool that improves visualization of neoplastic changes in the bronchial mucosa. The major aim of our study was to determine sensitivity and specificity of the technique in the assessment of tumor extent (margins). The secondary objective was to evaluate the possible effect of AFI on the change in therapeutic decisions of lung cancer treatment.In this prospective trial, we enrolled 104 patients in whom we performed 624 targeted biopsies, 3 from the pathologically altered mucosa (red-brownish or magenta colored) and 3 from randomly picked normal areas. We were using the Olympus BF-F260 videobronchoscope and EVIS LUCERA system. White light videobronchoscopy (WLB) preceded AFI examination and biopsy collection. All biopsy specimens were examined by a pathologist blinded to bronchoscopy findings, and where applicable surgically resected specimens were examined.In 14.4% of the patients, AFI revealed a greater extent of the tumor than WLB, and in 11.5% that finding led to change in therapeutic decision (lesser or greater resection or avoidance of surgery). We found a significant correlation between tumor extent determined by AFI and changes in therapeutic decisions (P < 0.01). Sensitivity, specificity, positive predictive value and negative predictive value for AFI in the assessment of tumor extension were 93%, 92%, 92% and 93%, respectively. Corresponding results for WLB were 84%, 79%, 77% and 85%, respectively. Relative sensitivity of AFI is 1.11.Our results confirm that AFI videobronchoscopy significantly improves the assessment of central lung cancer extension and influences the therapeutic strategy. This technique has greater sensitivity and specificity, in assessment of tumor margins, than WLB alone.